Red Spinach Extract Supplementation Improves Cycle Time Trial Performance in Recreationally Active Men and Women. Issue 9 (September 2021) - Gonzalez, Adam M.; Accetta, Matthew R.; Spitz, Robert W.; Mangine, Gerald T.; Ghigiarelli, Jamie J.; Sell, Katie M.
Abstract : Abstract: Gonzalez, AM, Accetta, MR, Spitz, RW, Mangine, GT, Ghigiarelli, JJ, and Sell, KM. Red spinach extract supplementation improves cycle time trial performance in recreationally active men and women. J Strength Cond Res 35(9): 2541–2545, 2021—To examine the effects of short-term red spinach extract (RSE) supplementation on cycling time trial performance, 17 recreationally active men ( n = 9, 22.2 ± 3.8 years) and women ( n = 8, 22.8 ± 3.5 years) underwent 2 testing sessions administered in a randomized, counterbalanced, double-blind fashion. Subjects were assigned to supplement daily with 1 g of RSE or placebo (PL) for 7 days priorly and 1 hour before completing a 4-km cycling time trial test. Performance variables (time-to-completion, average power, relative power, cadence, and average speed), subjective measures (perceived exertion and muscle fatigue), heart rate, and blood pressure were assessed during each testing session. Compared to PL, RSE supplementation significantly lowers ( p = 0.017, (Equation is included in full-text article.) = 0.24) post-exercise diastolic blood pressure (66.1 ± 6.1 vs. 70.1 ± 5.0 mm Hg). Red spinach extract supplementation also significantly improved ( p ⩽ 0.022, (Equation is included in full-text article.) = 0.30–0.37) 4-km completion time (404.6 ± 24.6 vs. 410.6 ± 31.3 seconds), average power (185.9 ± 32.2 vs. 181.6 ± 35.1 W), relative power (2.53 ± 0.44 vs. 2.46 ± 0.40 W·kg −1 ), and average speed (35.7 ± 2.2 vs. 35.3 ± 2.5 km·h −1 ). In addition, significant trial × sex interactions ( p ⩽ 0.022, (Equation is included in full-text article.) = 0.30–0.36) were observed for these performance measures, whereby only women showed significant improvement during RSE compared with PL trials. In conclusion, RSE supplementation significantly reduced time-to-completion, increased measures of power and speed, and lowered post-exercise diastolic blood pressure during a 4-km cycling time trial without altering subjects' perceived exertion or subjective measures of muscle fatigue. Finally, it is possible that women may be more responsive in regard to increasing performance after supplementation.